First Report of Soft Rot Caused by Pectobacterium brasiliense on Cucumber in Korea - Soo-Min Hong; Kyoung-Taek Park; Leonid N. Ten; Chang-Gi Back; In-Kyu Kang; Seung-Yeol Lee; Hee-Young Jung (Research in Plant Disease, 2023)
Wilted and water-soaked lesion symptoms were observed on cucumbers in greenhouses located in Daejeon, Chungcheongnam-do, Korea, in June 2021. A bacterial strain, designated KNUB-04-21, was isolated from the cucumbers, which was subsequently identified as Pectobacterium brasiliense through a phylogenetic analysis based on sequences of the 16S rRNA region, dnaX, leuS, and recA genes. The biochemical characteristics of KNUB-04-21 were also similar to those of P. brasiliense through investigation using the API ID 32 GN system. The pathogenicity of KNUB-04-21 was confirmed by inoculating it into healthy cucumber plants. The reisolated strains were also found to be same to the original strain. To our knowledge, this is the first report of P. brasiliense being identified as the causative agent of cucumber soft rot in Korea.